Postsecondary Inuit Students From Nunavut Pathways: When Students’ Satisfaction Meets Language Discrimination - Rodon, Thierry; Ratel, Jean-Luc; Gross, Pamela Hakongak; Lévesque, Francis; Okalik, Maatalii (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2021)
We present a multiple correspondence analysis (MCA) based on a survey of 362 Inuit students and graduates from Nunavut who attended college or university in Canada. Most participants reported that they were satisfied with their postsecondary educational experience and that postsecondary education had greatly improved their income and job outcomes. Results also show that postsecondary education clearly contributes to capacity building: Half of the participants reported working in their communities, and a majority said they wanted to work there. Nevertheless, some issues still need to be addressed by policymakers, the most notable being gender inequality in terms of job status, systemic discrimination against Inuit language speakers in the educational system, and the need to provide more access to postsecondary education.